Navigating the biphasic lucid power of subconscious mind: A dysfunction or holism in disguise? - Maham Khan (Journal of the Pakistan Medical Association, 2026)
Dear Editor, While there is a growing interest towards subconscious phenomena globally, experiences like lucid dreaming are under-researched in South Asia and remain largely unrecognized in Pakistan’s academic and clinical settings despite their widely acknowledged psychological significance. International studies have examined the association between lucid dreaming and psychopathology with quantified correlations and validated scales; however, there remains a stark lack of region-specific data in Pakistan, highlighting a critical research gap. Lucid dreaming is a unique state where subconscious and conscious minds interact, marked by self-awareness within a dream, where an individual may control the dream trajectory or their responses. EEG records show high frequency gamma waves during REM sleep which are associated with higher cognitive function, and hyperactivity in the prefrontal cortex and temporoparietal regions, which are generally hypoactive during normal sleep. LD may indicate underlying neuroticism, linked to increased susceptibility to stress, anxiety and depression. High LD frequency is observed in narcolepsy patients1 and individuals suffering from PTSD. Yet an interesting point owing to the intricate nature of LD is that it may represent a subconscious coping mechanism adopted by the brain to alleviate high distress levels, which highlights its therapeutic potential.2 Awareness in LD can be used to overcome narcoleptic nightmares and traumatic experiences as LD internalizes one’s locus of control,3 barricading external influences. However, LD cannot be considered overtly positive given its ties with psychosis,4 as the dreamer, being fixated on controlling their dream, may lose grip on external reality. False awakening, where the dreamer cannot differentiate between real awakening from waking up within a dream, is linked to lucidity and can lead to a distorted perception of reality. Deliberate induction of lucidity via techniques like WILD and WBTB, etc., can disrupt sleep-wake boundaries, leading to dissociation tendencies and schizotypy.5 LD may serve as a non-verbal flag of emotional dysregulation and so requires addressing in medical discourse and public awareness campaigns. Subconscious indicators should be included as supplementary tools alongside other validated tests in psychological screening for early assessment. Cross-sectional and pilot studies should be conducted at a regional level to assess prevalence, especially in high-stress populations like students where early signs often go unnoticed, along with assessment of cultural factors like authoritative parental control compelling students to resort to LD control. LD within moderation can serve as an affordable form of holistic psychotherapy; however, individuals must be discouraged from long-term lucidity induction practices. It is critical to understand this subconscious phenomenon for health practitioners to recognize when LD becomes particularly problematic.